ANALISIS FAKTOR-FAKTOR PENYEBAB KEMISKINAN DI KABUPATEN MUSI BANYUASIN (StudiKasus di kecamatan Sungai Lilin) - Mohd. Kurniawan. DP (Jurnal Ilmiah Ekonomi Global Masa Kini)
The phenomenon of poverty can not be avoided, but development has decreased the number of poor people but has not been able to eliminate poverty. It is time for poverty alleviation programs on the factors that influence it, because the factors causing poverty each region have different characteristics, thus efforts to alleviate poverty are also different.The data were collected by direct interview with respondent using questionnaire, samples were taken by using Slovin formula taken from Household data of Social Protection objective year 2017. The analysis result showed 86% of household heads were at productive age, 87% education of head of family did not finish junior high, Education is insignificant. Families, no significant family allowances. The role of local government is very important because more features of poverty in the region so that poverty alleviation programs are prepared in accordance with the characteristics of the region. To overcome the low education of poor families needed improvement and improvement. The orientation of education is directed at creating graduates who are able to become entrepreneurs and create jobs. Various training is required for additional skill enhancement and the development of productive assets in return for capital assistance.Key words : poverty, education, employment, number and income of family members